Needs Analysis for The Development of Teaching Materials in High School - Bonet, Rizma Melisa; Sumah, Astrid Sri Wahyuni; Saputri, Wulandari (Bioilmi: Jurnal Pendidikan, 2025)
Teachers facilitate students in understanding the material taught to achieve competence optimally. Making digital teaching materials is needed to achieve the objectives of the 2013 curriculum. The purpose of this study is to analyze the needs of students and teachers for teaching materials needed in schools. This research is descriptive research with the research subjects of X1.4 and X1.9 class students and 3 teachers of SMA 11 Palembang. The research data were obtained from filling out a questionnaire to analyze the initial needs of the type of teaching materials used. The results of the questionnaire analysis stated that the critical thinking skills of students were still low. The teaching materials used so far are textbooks and are considered not to support the learning process. The learning method applied by the teacher is still in the form of assignments, so it has not directed students to problem-solving. In addition to not using a learning model, teachers also have not used learning approaches such as STEAM, which emphasizes learning in aspects of science, technology, engineering, art, and mathematics.